History of Precedent: African American Voting Rights in the United States Supreme Court from the Reconstruction Era to Shelby County v. Holder - Grönroos, Viki (My University, 2026)
This bachelor’s thesis explores the history of African American voting rights in U.S. Supreme Court jurisprudence with particular attention to equal sovereignty of states doctrine. I will analyse how the Court’s interpretation of federalism has shaped the protections for Black voting rights. Using case genetics method enables me to track the evolution of African American enfranchisement from the failed promises of racial equality made in the Reconstruction era to the triumph of Civil Rights Movement and finally, to the current legal state. I will closely examine four landmark cases: Shelby County v. Holder (2013), South Carolina v. Katzenbach (1966), Giles v. Harris (1903) and United States v. Cruikshank (1876). My findings illustrate the Court’s contradictory role in the ongoing struggle for minority voting rights and reveal a persistent tension between state autonomy and individual rights.

Tämä notaarityö analysoi afroamerikkalaisten äänioikeuden historiaa Yhdysvaltojen korkeimman oikeuden oikeuskäytännössä, erityisesti suhteessa osavaltioiden itsemääräämisoikeuden periaatteeseen. Analysoin, kuinka tuomioistuimen tulkinta federalismista on vaikuttanut mustien äänioikeuden suojaan. Seuraan afroamerikkalaisten äänioikeuden tilan kehitystä jälleenrakentamiskauden petetyistä lupauksista kansalaisoikeusliikkeen menestyksen aikaan ja lopulta nykytilaan case genetics -menetelmän avulla. Tarkastelen lähemmin neljää merkittävää oikeustapausta: Shelby County v. Holder (2013), South Carolina v. Katzenbach (1966), Giles v. Harris (1903) ja United States v. Cruikshank (1876). Tutkimukseni tulokset valottavat korkeimman oikeuden ristiriitaista roolia taistelussa vähemmistöjen äänioikeuden puolesta ja paljastavat jatkuvan jännitteen, joka kulkee osavaltioiden autonomian ja yksilön oikeuksien välillä.
Keywords: U.S. Constitutional Law; Shelby County v. Holder; the Voting Rights Act of 1965; voting rights; equal sovereignty of states doctrine